2022
DOI: 10.1038/s41390-022-02275-6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and vitamin D receptor FokI polymorphism as risk factors for COVID-19

Abstract: Background Given the sparse data on vitamin D status in pediatric COVID-19, we investigated whether vitamin D deficiency could be a risk factor for susceptibility to COVID-19 in Egyptian children and adolescents. We also investigated whether vitamin D receptor (VDR) FokI polymorphism could be a genetic marker for COVID-19 susceptibility. Methods One hundred and eighty patients diagnosed to have COVID‐19 and 200 matched control children and adolescents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Vitamin D’s biological effects are mediated via its nuclear receptor, which serves as a ligand-activated transcription factor [ 16 ]. Even though the Vitamin D receptor (VDR) is abundantly expressed in lung tissue, the possible significance of vitamin D–VDR signaling in pulmonary immunopathology is unknown [ 17 ]. The highly polymorphic VDR gene encodes VDR.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D’s biological effects are mediated via its nuclear receptor, which serves as a ligand-activated transcription factor [ 16 ]. Even though the Vitamin D receptor (VDR) is abundantly expressed in lung tissue, the possible significance of vitamin D–VDR signaling in pulmonary immunopathology is unknown [ 17 ]. The highly polymorphic VDR gene encodes VDR.…”
Section: Introductionmentioning
confidence: 99%
“…However, similar to our study, no relationship was found between Fok1 polymorphism and the prevalence of COVID-19. The study by Zeidan et al from Egypt found that the FF genotype of Fok1 was significantly higher in COVID-19 patients, and patients with this genotype showed a higher susceptibility to COVID-19 infection (29). Ethnic group differences could explain discrepancies between the study results.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies classified patients according to their serum 25(OH)D level of sufficiency, and variations were noted between the values defined as sufficient, insufficient, and deficient. Studies included in our systematic review determine vitamin D deficiency as levels of serum 25(OH)D less than 20 ng/mL (<50 nmol/L) [16][17][18], less than 12 ng/mL (<30 nmol/L) [9], or between 5 and 15 ng/mL [19], mild deficiency as of 21-30 ng/mL [20], and mild to moderate deficiency as of 10-24 ng/mL [21]. Two studies defined severe vitamin D deficiency as 25(OH)D levels below 10 ng/ml [21,22], and one study as less than 5 ng/mL [19].…”
Section: Findings Of the Included Studiesmentioning
confidence: 99%